Better English, Better Job Opportunities in Nepal - Khadka, Kabita (Koshi Pravah: Multidisciplinary Peer Reviewed Journal, 2022)
Globalization paved the way for the rapid expansion of the English language and because of this, its horizons are being expanded day by day. This paper is an attempt to highlight and argue on the importance of the English language in higher education in Nepal in one hand and on the other hand, it tries to shed some light on the vocational zones that the English language has created in the country. The study is argumentative (qualitative) in nature and it has collected pieces of evidence of the English language’s popularity and its facilitation in higher education using secondary sources of data. The major findings comprise that the English language has provided an enormous contribution to the vocational zones and because of which all the universities in Nepal have adopted the English language for teaching and learning activities, new and new employment opportunities are facilitated, it is a key component for getting an education in English speaking countries, and an English-speaking person deserves good status in almost all countries in the world.